Knowing Where You're Going: Information Systems for Agricultural Research Management - Vernon, Richard (ISNAR and CTA, 2001)
This book provides agricultural research managers and information specialists within agricultural research organizations with a rich source of ideas, concepts, methodologies, and explanations in managing information. It provides guidance to those in agricultural research management setting out to harness the potentially enormous benefits of information and communications technology, to minimize the risks and maximize the benefits. The book draws on the experience of many information system implementations and implementers, both within and beyond agricultural research.